The effect of N- or C-terminal alterations of the connector of bacteriophage phi29 DNA packaging motor on procapsid assembly, pRNA binding, and DNA packaging - Cai, Ying (2008)
Double-stranded DNA viruses package their genomes into procapsids via an ATP-driven nanomotor. This ingenious motor configuration has inspired the development of biomimetics in nanotechnology. Bacteriophage ϕ29 DNA-packaging motor has been a popular tool in nanomedicine. To provide information for further motor modification, conjugation, labeling, and manufacturing, the connector protein gp10 of the ϕ29 DNA packaging motor was truncated, mutated, and extended. A 25-residue deletion or a 14-residue extension at the C terminus of gp10 did not affect procapsid assembly. A 42–amino acid extension at the N terminus did not interfere with the procapsid assembly but significantly decreased the DNA-packaging efficiency. DNA-packaging activity was restored upon protease cleavage of the extended region. Replacing the N-terminal peptide containing arginine and lysine with a histidine-rich peptide did not affect procapsid assembly but completely inhibited the packaging RNA (pRNA) binding to the connector and hindered subsequent DNA packaging. These results indicate that (1) the N-terminal arginine-lysine residues play a critical role in pRNA binding but are not essential for procapsid assembly; (2) the connector core, but not the flexible N- or C-terminal domains, is responsible for signaling the procapsid assembly; (3) pRNA binds to the connector as a result of electrostatic interactions between the polyanionic nature of nucleic acids and the cationic side groups of the amino acids, similar to RNA binding to Tat or polyArg.